Does Having a Chronic Liver Illness Make One More Likely to Become Melancholic and Anxious? - Osama Habib, Fahmina Ashaq, Nauman Ismat Butt, Khalid Mahmood, Azhar Ali Khan, Mohammad Atif Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic liver disease is a highly prevalent illness globally and in Pakistan as well. The current study was designed to investigate the prevalence of anxiety and depression in patients with chronic liver disease (CLD) in hospitalized patients. Methods and materials: Agha khan University anxiety and depression scale (AKUADS), a questionnaire developed natively in Urdu language, was the instrument used for the study. Admitted patients with the diagnosis of chronic liver disease at a tertiary care hospital in Lahore were invited to take part in the study. A total of 107 patients volunteered to take part in the study (29.9% females) from February 2018 to November 2018. Descriptive statistics was employed to report the prevalence of anxiety and depressive disorders in the study population and independent samples T-test was used to analyze the gender difference between the participants. Results: All study participants scored above the cut-off score of 20 on AKUADS. No significant gender difference was seen among the study participants on mean AKUADS scores. Conclusions: The prevalence of depressive and anxiety disorders is very high in patients with CLD. These patients should be assessed for the presence of depressive and anxiety symptoms on a frequent and routine basis. Recognition and treatment of depressive and anxiety symptoms at an early stage may lead to avoidance of many adverse outcomes related to CLD. Keywords: Depression, Anxiety, Chronic liver disease